2002
DOI: 10.1046/j.1365-2567.2002.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome‐proliferator‐activated‐receptor gamma (PPARγ) independent induction of CD36 in THP‐1 monocytes by retinoic acid

Abstract: SUMMARYRetinoic acid (RA) has been shown to regulate cellular growth and differentiation of a variety of cell types, including cells of the myelomonocytic lineage. We used the monocytic leukaemia cell line THP-1, which differentiates to macrophages in response to phorbol 12-myristate 13-acetate (PMA), to investigate the regulation by RA of genes in the scavenger receptor type B family (CD36) in human monocyte/macrophages. Reverse transcription-polymerase chain reaction and flow cytometry demonstrated that, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…To amplify 474 bp PPAR␥, 354 bp p21, 323 bp cyclin D1, and 200 bp glyceraldehyde-3-phosphate dehydrogenase cDNA fragments, the sequences of PCR primers (Sigma Genosys, Woodlands, TX) were as follows: for PPAR␥ sense (5Ј-CTCTCCGTAATGGAAGACC-3Ј), antisense (5Ј-GC-ATTATGAGACATCCCCAC-3Ј); for p21 sense (5Ј-GCGAT-GGAACTTCGACTTTGT-3Ј), antisense (5Ј-GGGCTTCCTCT-TGGAGAAGAT-3Ј); for cyclin D1 sense (5Ј-GGCAACGGA-GGTCTGCG-3Ј), antisense (5Ј-GTCGGTGGTAGATGCACA-GCTT-3Ј); and for glyceraldehyde-3-phosphate dehydrogenase sense (5Ј-CCATGGAGAAGGCTGGGG-3Ј), antisense (5Ј-CA-AAGTTGTCATGGATGACC-3Ј) according to published data (31)(32)(33). RT-PCR was carried out as described previously (31). The samples were first denatured at 95°C for 30 s, followed by 32 PCR cycles, each with temperature variations as follows: 95°C for 30 s, 60°C for 30 s, and 72°C for 30 s. The last cycle was followed by an additional extension incubation of 7 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…To amplify 474 bp PPAR␥, 354 bp p21, 323 bp cyclin D1, and 200 bp glyceraldehyde-3-phosphate dehydrogenase cDNA fragments, the sequences of PCR primers (Sigma Genosys, Woodlands, TX) were as follows: for PPAR␥ sense (5Ј-CTCTCCGTAATGGAAGACC-3Ј), antisense (5Ј-GC-ATTATGAGACATCCCCAC-3Ј); for p21 sense (5Ј-GCGAT-GGAACTTCGACTTTGT-3Ј), antisense (5Ј-GGGCTTCCTCT-TGGAGAAGAT-3Ј); for cyclin D1 sense (5Ј-GGCAACGGA-GGTCTGCG-3Ј), antisense (5Ј-GTCGGTGGTAGATGCACA-GCTT-3Ј); and for glyceraldehyde-3-phosphate dehydrogenase sense (5Ј-CCATGGAGAAGGCTGGGG-3Ј), antisense (5Ј-CA-AAGTTGTCATGGATGACC-3Ј) according to published data (31)(32)(33). RT-PCR was carried out as described previously (31). The samples were first denatured at 95°C for 30 s, followed by 32 PCR cycles, each with temperature variations as follows: 95°C for 30 s, 60°C for 30 s, and 72°C for 30 s. The last cycle was followed by an additional extension incubation of 7 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…16 By contrast, the blockage of CD36 reduced the secretion of IL-1β, IL-6 and IL-8 and foam cell formation in human macrophages. 17 Based on the results of the above studies, it can be concluded that reduction of CD36 receptor expression on macrophages prevents the development of atherosclerosis. This has opened up the scope for further research on the regulation of CD36 expression to prevent atherosclerosis in humans.…”
Section: Plateletsmentioning
confidence: 97%
“…The treatment affected as expected the expression of genes previously shown to be modulated by ATRA in adipocytes and/or adipose tissue ( Table 1 ), which validated our microarray experiments. Thus, changes brought about by ATRA treatment included the induction of Rar ␤ , Rarres1, Ucp1 and 2, Ppargc1 ␣ , Ppar ␣ , or Cyp26b1 and the repression of the leptin, resistin, Cebp ␣ , adiponectin, and Rxr ␣ genes ( 4,9,15,18,(24)(25)(26)(27).…”
Section: Animal Experimentsmentioning
confidence: 99%